Robo-advisor Can Play A Role In Promoting Financial Knowledge Within Society - Nur Shuhada Kamarudin; Noradilah Abdul Hadi; Azuan Ahmad; Azreen Jihan Che Mohd Hashim; Ahmad Fadly Nurullah Rasedee; Muhammad Zikry Hishamudin; Nazam Dzolkarnaini (Semarak Ilmu Publishing, 2024)
Indexed by MyCite